2010
DOI: 10.1007/s10750-010-0291-y
|View full text |Cite
|
Sign up to set email alerts
|

Current and substrate preferences of benthic invertebrates in the rivers of the Hindu Kush-Himalayan region as indicators of hydromorphological degradation

Abstract: The study introduces an approach to obtaining information about the preferences of benthic invertebrates for substrate and current velocity in a region with little prior knowledge of benthic invertebrates. These preferences are then used for river assessment. Substrate-specific sampling of 271 reference sites was conducted in lower mountainous and lowland areas of the Hindu Kush-Himalaya region. Statistical analysis revealed significant preferences for substrate type and current velocity for 50 taxa of Ephemer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Armanini et al (2010) developed a flow sensitivity index for Canada and used freshwaterecology.info content for validation purposes. Korte (2010) compared the current and substrate preference of indicators developed for the Hindu Kush-Himalayan region with preferences of European species. Von Bertrab et al (2013) used functional traits to assess species' responses to fine sediment input.…”
Section: Biomonitoring and Assessment Systemsmentioning
confidence: 99%
“…Armanini et al (2010) developed a flow sensitivity index for Canada and used freshwaterecology.info content for validation purposes. Korte (2010) compared the current and substrate preference of indicators developed for the Hindu Kush-Himalayan region with preferences of European species. Von Bertrab et al (2013) used functional traits to assess species' responses to fine sediment input.…”
Section: Biomonitoring and Assessment Systemsmentioning
confidence: 99%
“…The main factor affecting the composition of riverine macroinvertebrates is water current; i.e., determining the presence or absence of limnetic or lotic taxa [4][5][6][7]. The velocity of the current indirectly affects water retention time, which is one of the most important factors shaping the physicochemical conditions and qualitative and quantitative structure of all aquatic organisms [1].…”
Section: Introductionmentioning
confidence: 99%
“…Early work showed that Plecoptera have a clear preference for colder streams and lakes; their distribution in warmer streams is much more restricted (Baumann, 1979). Similarly, Plecoptera have often been identified as having specific hydraulic flow preferences, with a general preference for higher flows (rheobiont), but ability to tolerate standing waters (limnobiont) in some groups so long as temperatures are low (Mérigoux et al, 2009;Korte, 2010;Tierno de Figueroa et al, 2010).…”
Section: Discussionmentioning
confidence: 99%